Interaction Effects of AFB1 and MC-LR Co-exposure with Polymorphism of Metabolic Genes on Liver Damage: focusing on SLCO1B1 and GSTP1. Issue 1 (December 2017) - Yang, Xiaohong; Liu, Wenyi; Lin, Hui; Zeng, Hui; Zhang, Renping; Pu, Chaowen; Wang, Lingqiao; Zheng, Chuanfen; Tan, Yao; Luo, Yang; Feng, Xiaobin; Tian, Yingqiao; et al.
Abstract AFB1 and MC-LR are two major environmental risk factors for liver damage worldwide, especially in warm and humid areas, but there are individual differences in health response of the toxin-exposed populations. Therefore, we intended to identify the susceptible genes in transport and metabolic process of AFB1 and MC-LR and find their effects on liver damage. We selected eight related SNPs that may affect liver damage outcomes in AFB1 and MC-LR exposed persons, and enrolled 475 cases with liver damage and 475 controls of healthy people in rural areas of China. The eight SNPs were genotyped by PCR and restriction fragment length polymorphism. We found that SLCO1B1 (T521C) is a risk factor for liver damage among people exposed to high AFB1 levels alone or combined with MC-LR, and that GSTP1 (A1578G) could indicate the risk of liver damage among those exposed to high MC-LR levels alone or combined with high AFB1 levels. However, GSTP1 (A1578G) could reduce the risk of liver damage in populations exposed to low MC-LR levels alone or combined with high AFB1 levels. In conclusion, SLCO1B1 (T521C) and GSTP1 (A1578G) are susceptible genes for liver damage in humans exposed to AFB1 and/or MC-LR in rural areas of China.